Evaluation of the relationship between nutrition literacy, Mediterranean diet compliance, ecological footprint and sustainable environmental attitudes in adolescents - Özge Mengi Çelik; Emine Merve Ekici; Selin Yılmaz; Ziya Erokay Metin (BMC Public Health)
Abstract Objective This study aimed to evaluate the relationship between nutrition literacy, Mediterranean diet compliance, ecological footprint and sustainable environmental attitudes in adolescents. Methods This descriptive and cross-sectional study was conducted with 673 adolescents aged 14–18 years. The individuals' general characteristics were questioned. Sustainable environmental attitudes, nutritional literacy status and compliance with the Mediterranean diet were assessed with the help of scales. An ecological footprint calculator was used for the calculation of the ecological footprint. Results The mean age of the individuals was 16.5 ± 1.42 years. Adolescent Nutrition Literacy Scale score and Sustainable Environmental Attitude Scale score were higher in female adolescents than in males (p < 0.05). Ecological Footprint score was higher in male adolescents than in females (p < 0.05). A statistically significant positive correlation was found between Adolescent Nutrition Literacy Scale score, Sustainable Environmental Attitude Scale score and Mediterranean Diet Quality Index (KIDMED) score (p < 0.05). It was determined that sex and Sustainable Environmental Attitude Scale score affected the Ecological Footprint total score (p < 0.05). It was determined that sex, Adolescent Nutrition Literacy Scale score and Ecological Footprint total score affected the Sustainable Environmental Attitude Scale score (p < 0.05). Also, it was determined that Adolescent Nutrition Literacy Scale score affected the KIDMED score (p < 0.05). Conclusions Girls have higher nutritional literacy and sustainable environmental attitude. Nutrition literacy, sustainable environmental attitude and KIDMED total scores showed a significant positive correlation with each other. Nutritional literacy is effective on sustainable environmental attitude and compliance with the Mediterranean diet. Sustainable environmental attitude is effective in reducing the ecological footprint.